The Impact Of Herding Behavior, Heuristic Behavior, Disposition Effect, And Attitudes Toward Risk On Stock Market Investment Decisions - Fitria Rahmadhani; Muhammad Fuad; Muhammad Rizal (Doctoral Program of Social Science Pasundan University, 2026)
This study aims to analyze the influence of herding behavior, heuristic behavior, disposition effect, and attitudes on risk on investment decisions in the stock market. This study uses a quantitative approach with a non-probability sampling technique through a purposive sampling method. The population in this study is individual stock investors in Indonesia whose exact number is unknown. The sample used was 101 respondents. Data collection was carried out through questionnaires. The data analysis method used was multiple linear regression with t-test, F-test, and coefficient of determination test. The results show that herding behavior has a significant positive effect on investment decisions, heuristic behavior has a significant negative effect on investment decisions, disposition effect has no significant effect on investment decisions, while attitudes on risk have a significant positive effect on investment decisions. The coefficient of determination value indicates that a relatively large variation in investment decisions is explained by the variables analyzed in this study.